Python in a nutshell - Martelli, Alex; Ravenscroft, Anna Martelli; Holden, Steve, 1950- (Sebastopol, CA : O'Reilly Media, 2017)
This book provides a quick reference to the language, including Python 3.5, 2.7 and highlights of 3.6. It covers a wide range of application areas, including web and network programming, XML handling, database interactions, and high-speed numeric computing
Introduction to Python -- The Python interpreter -- The Python language -- Object-oriented Python -- Exceptions -- Modules -- Core built-ins and standard library modules -- Strings and things -- Regular expressions -- File and text operations -- Persistence and databases -- Time operations -- Controlling execution -- Threads and processes -- Numeric processing -- testing, debugging, and optimizing -- Network basics -- Asynchronous alternatives -- Client-side network protocol modules -- Serving HTTP -- Email, MIME, and other network encodings -- Structured text: HTML -- Structured text: XML -- Extending and embedding classic Python -- Distributing extensions and programs -- v2/v3 migration and coexistence.
Includes bibliographical references and index.
CSE
Book Finder International
Keywords: Python (Computer program language).; Scripting languages (Computer science).; COMPUTERS / Programming Languages / Python; COMPUTERS / Programming / Object Oriented; COMPUTERS / Reference; Scripting languages (Computer science); Python (Computer program language); Python 2.7; Python 3.5; Python 3.6